Factors affecting mathematics performance among ordinary secondary school students in Tanzania and its implications for future career selection: A review of literature - Kalemile, Dorence M.; Katabwa, Johnson N. (African Quarterly Social Science Review, 2026)
Performance in the mathematics discipline has been a stumbling block among students completing ordinary secondary schools in Tanzania. The discipline has been showing inefficient results among the finalists of secondary school from year to year despite its importance. This study aimed at analyzing major factors contributing to the subject matter not being well understood among students. The study was conducted in Tanzania purposively in order to meet its objective and guided by the Expectancy Theory of Motivation. The theory posits that students’ individual motivation and intensity of work are highly affected by their future’s expectations. The study adopted a systematic literature review with the sample involving 22 studies. Data were collected from authentic secondary data sources and analyzed using descriptive statistics. Factors with higher frequencies were adopted as major contributing factors of performance in mathematics in the study area. The study found that mathematics in secondary schools was faced with factors of four categories, i.e., policy-related factors, individual factors, psychological factors, and socio-economic factors. The policy-related factors were major contributing factors to the current problem by 60%. The study concluded that the mathematics subject is seriously faced with a lot of issues, but the leading factors are related to education policy. Solving policy-related factors will mean improving performance in mathematics. The study recommends the Ministry of Education and other education stakeholders come up with a special project/program purposely to improve performance in the subject matter.